Experimental and numerical investigations into the transient multi-wafer batch atomic layer deposition process with vertical and horizontal wafer arrangements. (December 2015) - Pan, Dongqing; Ma, Lulu; Xie, Yuanyuan; Wang, Fenfen; Jen, Tien-Chien; Yuan, Chris
Highlights: Vertical and horizontal wafer arrangements in multi-wafer batch ALD process are investigated. Vertical multi-wafer layout is superior to the horizontal arrangement in terms of film deposition rate. Surface reactions in ALD are completely terminated once surface species conversion comes to the end. Deposition process is under a joint influence of precursor concentration and surface sites saturation status. Position dependence of deposition rate in multi-wafer ALD is weak and negligible. Abstract: This paper investigates two types of wafer arrangements, vertical and horizontal, in a multi-wafer atomic layer deposition (ALD) reactor. The growth rate of ALD deposited alumina thin film is characterized and compared experimentally and numerically. It's found that the wafer layout influences the deposition process significantly. Vertical multi-wafer arrangement is shown superior to the horizontal arrangement in terms of film deposition rate because of the enhanced collisions between precursor molecules and wafer surfaces in vertical arrangement. Studies using three-dimensional transient numerical model of fluid dynamics and surface reaction kinetics in multi-wafer batch ALD reveal the self-limiting details on the physical and chemical nature of ALD process. First, the deposition process is shown highly "self-limited": surface reactions in ALD are completely terminated once surface species conversion comes to the end. Second, deposition process is found under a joint influence of precursor concentration and surface site saturation status. Before deposition rate reaches its peak, the precursor concentration is dominant in determining the deposition rate, but it is largely confined by the available surface reactive sites after the peak. Position dependence of deposition rate as shown by both experiments and simulations is weak and negligible.